Molecular cloning and functional expression of a Δ9-fatty acid desaturase from an antarctic Pseudomonas sp. A3 - Garba, Lawal; Mohamad Ali, Mohd Shukuri; Oslan, Siti Nurbaya; Raja Abdul Rahman, Raja Noor Zaliha (Public Library of Science, 2016)
Fatty acid desaturase enzymes play an essential role in the synthesis of unsaturated fatty acids. Pseudomonas sp. A3 was found to produce a large amount of palmitoleic and oleic acids after incubation at low temperatures. Using polymerase Chain Reaction (PCR), a novel Δ9- fatty acid desaturase gene was isolated, cloned, and successfully expressed in Escherichia coli. The gene was designated as PA3FAD9 and has an open reading frame of 1,185 bp which codes for 394 amino acids with a predicted molecular weight of 45 kDa. The activity of the gene product was confirmed via GCMS, which showed a functional putative Δ9-fatty acid desaturase capable of increasing the total amount of cellular unsaturated fatty acids of the E. coli cells expressing the gene. The results demonstrate that the cellular palmitoleic acids have increased two-fold upon expression at 15°C using only 0.1 mM IPTG. Therefore, PA3FAD9 from Pseudomonas sp.A3 codes for a Δ9-fatty acid desaturase-like protein which was actively expressed in E. coli.